Implementation Of Online High School Online Acceptance Of New Students Policy At The Education Office Of North Sumatra Province - Afriani Rolenta Naibaho (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2022)
Implementation of the policy of New Student Acceptance (PPDB) Online is a process of implementing well-formulated education policy. Online PPDB Policy is used as a basis for implementing new student acceptance system by online. to assess the success of the implementation of PPDB Online policy can be seen from 2 major variables namely policy content and policy implementation environment. This objective is to find out how the implementation of the policy of acceptance of new learners (PPDB) Online and see the problems that arise when implementing the policies implemented by the Education Office of North Sumatra province.The research method used in this study is a qualitative approach in which the study was a descriptive study is to determine or describe the reality of events. Data collection techniques are Interviews, Observations, and documents related to the research. Data analysis techniques in this study were conducted qualitatively. This study uses nine policy implementation variables from Merilee S Grindle covering the interests of the target group, Type of benefits received, Degree of change, Location of decision making, Program implementers, Resources, power, interests, and strategies, Institutional characteristics, Compliance level .From the research, it can be concluded that the implementation of the policy of new student enrollment (PPDB) at the middle school level has been running well in terms of the content of the policy, the benefits received, the expected changes, the location of the decision and the Characteristics of Institutions and Regimes, The Power, Interest, And Strategy Of The Actors Involved. However, in terms of policy implementers, resources and compliance levels have not gone well. It is inhibiting the success of the implementation of the policy of new students (PPDB) Online.